ELUCIDATING APOSEMATIC PATTERNS IN NORTH AMERICAN HYLIDS - (:unkn) unknown (My University, 2023)
Recognizing form and function of animal defenses is paramount to understanding the ecological and evolutionary forces behind predator and prey dynamics. Color patterns are strongly related to defensive strategies in animals. Some rely on camouflage to avoid detection, while others are brightly colored and conspicuously signal their noxiousness to potential predators. Still others combine cryptic dorsal coloration with colorful patches that are concealed in resting position but are facultatively unveiled by special behavior or simply during activity. Such hidden conspicuous color patches may be an intermediate stage in the evolution from camouflage to aposematism. We investigated whether conspicuously colored thighs serve as an aposematic signal in members of the North American Hylid treefrog family. Many Hylids are generally considered to be cryptic, yet show colorful patches on their flanks or thighs and have defensive skin secretions that may have unpalatable properties. First we conducted a palatability study to test whether Gray Treefrog (Hyla versicolor) skin secretions are unpalatable to model predators, and a clay model field study to test whether the conspicuous black and yellow thigh pattern is an aposematic warning coloration that reduces predation. Frog secretions were discriminated against during palatability assays, and clay models painted with a spotted black and yellow pattern suffered lower predation rates. Second we investigated whether thigh color was indicative of palatability in nine species of Hylid. We found species with thigh colors to be significantly more unpalatable than members without. Our findings support the hypothesis that hidden color patches act as aposematic signals in Nearctic Treefrogs and suggests that more species benefit from aposematic coloration than currently appreciated.
Keywords: Aposematism; Defense; Fly; Frog; Palatability; Secretion